2017
DOI: 10.1007/s10518-017-0142-6
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of consistent hard rock (1000 < VS < 3000 m/s) GMPEs from surface and down-hole recordings: analysis of KiK-net data

Abstract: A key component in seismic hazard assessment is the estimation of ground motion for hard rock sites, either for applications to installations built on this site category, or as an input motion for site response computation. Empirical ground motion prediction equations (GMPEs) are the traditional basis for estimating ground motion while V S30 is the basis to account for site conditions. As current GMPEs are poorly constrained for V S30 larger than 1000 m/s, the presently used approach for estimating hazard on h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 54 publications
3
43
0
Order By: Relevance
“…For the sake of simplicity in the present exercise, the hazard curve has been derived with only one GMPE (Akkar et al, 2014) (AA14) [36], which is satisfactorily representative of the median hazard curve on rock obtained with seven other GMPEs deemed to be relevant for the European area (see [15]). The host-to-target (HTT) adjustments have been performed here on the basis of simple velocity adjustments calibrated on KiKnet data using the Laurendeau et al, 2107 GMPE [37], since the detailed knowledge of the site characteristics does not compensate the very poor information on the "host" characteristics of any GMPE (in particular those from European data), which results in very large uncertainty levels in classical HTT approaches [38].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the sake of simplicity in the present exercise, the hazard curve has been derived with only one GMPE (Akkar et al, 2014) (AA14) [36], which is satisfactorily representative of the median hazard curve on rock obtained with seven other GMPEs deemed to be relevant for the European area (see [15]). The host-to-target (HTT) adjustments have been performed here on the basis of simple velocity adjustments calibrated on KiKnet data using the Laurendeau et al, 2107 GMPE [37], since the detailed knowledge of the site characteristics does not compensate the very poor information on the "host" characteristics of any GMPE (in particular those from European data), which results in very large uncertainty levels in classical HTT approaches [38].…”
Section: Methodsmentioning
confidence: 99%
“…It is therefore mandatory to perform what is known in literature as "host-to-target adjustment" corrections (HTT [31][32][33][34]). As discussed in [14,15], the high level of complexity and uncertainty associated to the current HTT adjustments procedures [16,37,[49][50][51], have motivated us to use here another, simpler, straightforward way to account for rock to hard rock correction for probabilistic seismic hazard purposes.…”
Section: Host-to-target Adjustmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…State-of-the-art GMPEs require several site-specific parameters, used as 'proxys' in their functional forms. Laurendeau et al (2017) and Bora et al (2015Bora et al ( , 2017 took advantages of the availability of well-characterized strong motion databases (i.e., KikNet, Resorce, respectively) to propose alternative approaches to classical host-to-target corrections, mainly based on the Vs 30m and Kappa parameters. These studies showed that the host-to-target adjustment is particularly 'approach-sensitive', and results might vary widely.…”
Section: Site-specific Shamentioning
confidence: 99%